Literature Review: The Effects of Religiosity, Organizational Commitment, and Performance at the National Amil Zakat Agency (Baznas) - Utama, Indra; Laksmi, Asri; Novela, Intan (Eastasouth Institute, 2024)
In the past few decades, research on religiosity has become increasingly prevalent and extensive. Religiosity encompasses moral and ethical principles derived from religious teachings. The values of religiosity can influence employees' attitudes, behaviors, and commitment in the workplace. The aim of this research was to explore the association among religiosity, institutional commitment, together with employee performance, with a focus on religious practices in Islam, namely the five daily prayers (Salat) and voluntary acts of worship, including voluntary fasting a mong employees at the National Amil Zakat Authority (Baznas). The National Amil Zakat Authorrity is a state institution that collects and distributes zakat funds from contributors (muzakki) to recipients (mustahik) to help the government alleviate poverty. Using a literature review approach, this study examines relevant literature and other sources. The research identifies the effect of religiosity on institutional commitment and employee performance within the setting of the National Amil Zakat Authority. The study finds that religiosity, manifested through religious practices in Islam such as the five daily prayers and voluntary acts of worship, including voluntary fasting, significantly impacts employees' organizational commitment, thereby positively influencing organizational performance. The implications for further research are that this literature review provides opportunities for additional studies in this field. Further research could focus on specific aspects of religiosity, organizational commitment, and organizational performance, as well as explore additional variables that may moderate the relationships between these variables.